Integrated environmental evaluation of heavy metals and metalloids bioaccumulation in invertebrates and seaweeds from different marine coastal areas of sardinia, mediterranean sea. (November 2020) - Corrias, Francesco; Atzei, Alessandro; Addis, Piero; Secci, Marco; Russo, Mariateresa; Angioni, Alberto
Abstract: In this work, three gastropods Patella vulgata, Osilinus turbinata, and Tahis clavigera, one echinoderm Parancetrotus lividus, one coelenterate Anemonia sulcata, and two seaweed Padina pavonica, and Cystoseira mediterranea were collected from three different marine areas of Sardinia in the Mediterranean sea and studied for heavy metals and metalloid content and accumulation trends. Inductively coupled plasma optical emission spectrometry (ICP-OES) was used for the determination of Al, AS, B, Ba, Be, Cd, Co, Cr, Cu, Fe, Hg, Mn, Mo, Ni, Pb, Sb, Se, Sn, Sr, Te, Ti, V and Zn in the selected samples. The results showed that gastropods were capable of accumulating Al, Ba, Cu, Fe, Sr, and Zn; seaweeds can better concentrate Al, Fe, and Zn than all other species. At the same time, echinoderms and coelenterate had limited ability to store specific metals, showing a much more homogeneous distribution. PCA analysis allowed us to discriminate among the sites and the species. Cala Zafferano was the area with the higher values of accumulation of all metals in all species as expected, considering its proximity to industrial sites. The results of the analysis showed clearly that heavy metal and metalloid accumulation was different for each species studied. Therefore, for a correct environmental assessment of a given area, a comprehensive approach is strongly recommended by exploiting the different properties of both accumulation and concentration of the metals by different aquatic species. Graphical abstract: Image 1 Highlights: Different species showed different bioaccumulation rates. A correct environmental assessment of a given area need a heterogeneous approach. Among gastropods Thais accumulate more levels of Zn, Cu, Cd, and Mo. Seaweeds accumulate more levels of Pb, Al and Fe in respect to all other marine species. PCA analysis allowed to discriminate among the sites and among the species. Abstract : Different species of aquatic living organisms have different heavy metals and metalloid accumulation trends, even if they belong to the same family and the same water column or have similar living habits.